Ductus Arteriosus Stenting as a Method of Palliative Treatment of Truncus Arteriosus Type A3: Literature Review and Clinical Case - Tetyana Ye. Hura; Anzhelika O. Mykhailovska; Oleksandra O. Motrechko; Andrii V. Maksymenko (Український журнал серцево-судинної хірургії, 2023)
Introduction. Van Praagh A3 variant of truncus arteriosus (TA A3) is a condition when the one pulmonary artery branch origins from the TA, the other is filled through the patent ductus arteriosus (PDA).